White House Conference on Families Families and Human Needs. Delegate Workbook. - White House Conference on Families, Washington, DC.; White House Conference on Families, Washington, DC. ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1980)
This Delegate Workbook was intended as a resource for delegates to the White House Conference on Families (WHCF) in the hope that they would use it for the task of developing an "action agenda" to strengthen and support families. The workbook performs three basic functions for the delegates: (1) focuses attention on the themes of the WHCF; (2) provides brief background information on the issues discussed in the conference workgroups; and (3) summarizes recommendations for which there was consensus across several states. Five issue briefs provide background information in the areas of education, health, housing, child care, and handicapping conditions. The briefs are organized into four sections: Introduction; Background Information on Major Issues; Current Programs and Policies; and Recommendations from the States. Recommendations were classified by topic and issue. Similar recommendations were grouped together and a sample recommendation was selected for purposes of illustration. Recommendations listed were taken from state reports received by May 5, l980 and are provided as starting points for discussion among delegates. (Author/RH)
ERIC Note: For related documents, see PS 011 989-991 and ED 194 192.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Citizen Participation; Conferences; Day Care; Disabilities; Educational Needs; Family Health; Family Programs; Health Needs; Housing Needs; Policy; Policy Formation; Social Action; Social Problems; White House Conference on Families; Opinion Papers